The United Nations Security Council Reforms and The Permanent Five Challenge: A Historical Perspective (Journal of International Studies, 2015)
The manner in which the United Nations Security Council (UNSC) is presently constituted remains the greatest challenge to the realization of the ambitions of UNSC permanent seat seekers. For the highly infl uential economic giants better known as the â€œmiddle powersâ€- Japan, India, Brazil, and Germany; and African leading contenders such as Nigeria, South-Africa and Egypt ambitions to yield the desired result, they must mandatorily secure the support of the UNSC Permanent fi ve veto holding members. In light of the foregoing, this paper examines the attempts to reform the UNSC since the late 1960s and the roles of the Permanent fi ve members of the UNSC such as Britain, China, France, USA and Russia regarding this endeavour. Specifi cally, it argues that the Permanent fi ve memberâ€™s disposition to this issue has been the major challenge to the much desired reform of the UNSC. The UNSC is the main organ of the United Nations (UN) that is vested with powers to maintain international peace and security. Since its creation in mid 1940s, this organ has been criticized for its undemocratic nature by member states whose region are either not represented in the Security Council (SC) or under-represented.